2023
DOI: 10.2147/jhc.s428980
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial Chemoembolization Plus Lenvatinib and PD-1 Inhibitors for Hepatocellular Carcinoma with Main Trunk Portal Vein Tumor Thrombus: A Multicenter Retrospective Study

Shu-Qun Li,
Jun-Yi Wu,
Jia-Yi Wu
et al.

Abstract: Purpose In recent years, immune checkpoint inhibitors have been used in combination with tyrosine kinase inhibitors and local therapies, creating a new era in treating hepatocellular carcinoma (HCC) with portal vein tumor thrombus (PVTT). However, the benefits of this triple therapy remain unclear. Thus, this study evaluated whether the combination of transarterial chemoembolization (TACE), lenvatinib, and programmed death-1 (PD-1) inhibitors (triple therapy) was effective and safe for unresectabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The objective response rates were 2%, 24.1%, and 27.3% for sorafenib, lenvatinib, and atezolizumab plus bevacizumab group; Progression-free survival for sorafenib was 7.4 months, and 6.8 months for Atezolizumab plus Bevacizumab; The median overall survival was 10.7 months for sorafenib, 13.6 months for lenvatinib, 19.2 for Atezolizumab plus bevacizumab [ 13 , 19 , 21 , 46 ]. However, the main subgroup in a study was Vp4 PVTT, the PFS was 4.9 months, the OS was 9.4 months, and the objective response rate of PVTT based on mRECIST was 61.5% who received PD-1 inhibitor lenvatinib plus radiotherapy in previous study [ 47 ]; The intrahepatic tumor objective response rate was 68.3%, and the median OS, PFS was 21.7 months and 14.5 months for patients with main trunk portal vein tumor thrombus who received transarterial chemoembolization plus lenvatinib and PD-1 inhibitors [ 48 ]. The high ORR observed in patients receiving HAIC, lenvatinib, and PD-1 antibodies may be due to the synergistic antitumor effects of HAIC, lenvatinib, and PD-1 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The objective response rates were 2%, 24.1%, and 27.3% for sorafenib, lenvatinib, and atezolizumab plus bevacizumab group; Progression-free survival for sorafenib was 7.4 months, and 6.8 months for Atezolizumab plus Bevacizumab; The median overall survival was 10.7 months for sorafenib, 13.6 months for lenvatinib, 19.2 for Atezolizumab plus bevacizumab [ 13 , 19 , 21 , 46 ]. However, the main subgroup in a study was Vp4 PVTT, the PFS was 4.9 months, the OS was 9.4 months, and the objective response rate of PVTT based on mRECIST was 61.5% who received PD-1 inhibitor lenvatinib plus radiotherapy in previous study [ 47 ]; The intrahepatic tumor objective response rate was 68.3%, and the median OS, PFS was 21.7 months and 14.5 months for patients with main trunk portal vein tumor thrombus who received transarterial chemoembolization plus lenvatinib and PD-1 inhibitors [ 48 ]. The high ORR observed in patients receiving HAIC, lenvatinib, and PD-1 antibodies may be due to the synergistic antitumor effects of HAIC, lenvatinib, and PD-1 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is likely that the use of PBT in combination with agents such as lenvatinib will improve treatment outcomes. In recent years, several clinical trials have been conducted and reported on the combination of immune checkpoint inhibitors and PBT for HCC [ 48 , 49 ]. In Japan, several clinical trials and prospective studies of PBT for HCC have been conducted.…”
Section: Discussionmentioning
confidence: 99%